Actors of Education Supervision in Indonesia - Salafiyah, Yuyun; Farisi, Ahmad Nu'man; Supardi, Supardi; Gunawan, Agus (Asian Journal of Management Analytics, 2025)
Stakeholders are still concerned about supervision in education. Particularly since the Independent curriculum was introduced, all education-related laws have been modified or updated. The purpose of this essay is to investigate the theories that underpin monitoring as well as the laws and rules that control those who violate them. This study was written utilizing a qualitative approach that involved library research. It was discovered that the head of the education unit, the school/madrasah committee, the central government, and the local government all carry out education supervision in accordance with the most recent rules and regulations.